PENGGUNAAN MODEL PEMBELAJARAN BERBASIS PROYEK UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS 3 SD PADA MATERI MENGENAL SIKLUS PADA MAKHLUK HIDUP - Nurhayati (Lembaga PKBM Tunas Harapan Varoso, 2023)
This research aims to evaluate the implementation of Project-Based Learning (PjBL) to enhance the learning outcomes of third-grade elementary school students on the topic of understanding life cycles in living organisms. The research methodology employed is Classroom Action Research (CAR), involving 15 students as participants. The PjBL learning process is conducted in two cycles with structured steps, including determining main questions or issues, planning the project, scheduling project completion, monitoring progress, presenting project results, and evaluating the project process and outcomes. Data analysis involves comparing pre-test and post-test results in each cycle.The results of the research indicate a significant improvement in students' understanding of the